The mechanism and application of Scrophulariae Radix in the treatment of endocrine disorders: focusing on thyroid diseases and diabetes mellitus - Song, Jiaying; Li, Jiuwei; Shi, Huishan; Liu, Huayuan; Qu, Yuehan; Wang, Furong (Frontiers in Endocrinology, 2025)
Endocrine disorders are prevalent worldwide, with particularly high incidence rates of thyroid diseases and diabetes mellitus (DM), which impose a substantial burden on healthcare systems. Life-long medication is often required to manage these conditions. Scrophulariae Radix is a traditional Chinese medicine. It contains various chemical components, such as iridoids, phenylpropanoids, and organic acids. These components show anti-inflammatory, antioxidative, and immunomodulatory effects. They have potential to treat endocrine disorders. They are especially effective for thyroid diseases and DM. This review aims to summarize the mechanisms and effects through which Scrophulariae Radix affects thyroid diseases and DM, providing further guidance for clinical treatment.